Subclinical Hypothyroidism Prevalence and Selenium Levels in Women of North Khorasan, Iran: a Cross-Sectional Study - Kimiya Hadavi; Ali Esmaeili; Zeynab Moallemi; Javad Hashemi (Acta Clinica Croatica)
Individuals with subclinical hypothyroidism have an increased risk of developing clinical hypothyroidism. The thyroid gland, which has the highest concentration of selenium per gram of tissue among adults, plays a crucial role in the metabolism of thyroid hormones. This study aimed to investigate the prevalence of subclinical hypothyroidism in the North Khorasan province of Iran and assess the serum selenium levels in affected individuals. We conducted a prospective study involving 550 females aged 20-55. Serum samples were collected from individuals based on the study’s inclusion and exclusion criteria. We measured the serum levels of thyroid-stimulating hormone (TSH), thyroxine (T4), and triiodothyronine (T3). Subsequently, individuals with high TSH but normal T4 and T3 levels were selected for further analysis (group I). The serum levels of TSH, T4, T3 (using the ELISA method), and selenium (using the atomic absorption method) were measured and compared with those of a control group comprising healthy women matched to group I in terms of number, age, and body mass index. The overall prevalence of subclinical hypothyroidism in the study population was 6.48%. Significant differences were observed in serum TSH and selenium levels between the subclinical hypothyroidism group and the control group. Furthermore, a positive correlation between TSH and selenium levels was found exclusively within the subclinical hypothyroidism group. The occurrence of subclinical hypothyroidism was positively correlated with serum selenium levels.